Assessing Patient-reported Quality of Life Outcomes in Vulva Cancer Patients: A Systematic Literature Review. Issue 4 (1st May 2018) - Froeding, Ligita Paskeviciute; Greimel, Elfriede; Lanceley, Anne; Oberguggenberger, Anne; Schmalz, Claudia; Radisic, Vesna Bjelic; Nordin, Andy; Galalaei, Razvan; Kuljanic, Karin; Vistad, Ingvild; Schnack, Tine Henrichsen; Jensen, Pernille Tine
Abstract : Objectives: Vulva cancer (VC) treatment carries a high risk of severe late effects that may have a negative impact on quality of life (QoL). Patient-reported outcome measures (PROMs) are increasingly used when evaluating disease- and treatment-specific effects. However, the adequacy of measures used to assess sequelae and QoL in VC remains unclear. The aims of the present study were to evaluate disease- and treatment-related effects as measured by PROMs in VC patients and to identify available VC-specific PROMs. Methods/Materials: A systematic literature search from 1990 to 2016 was performed. The inclusion criterion was report of disease- and treatment-related effects in VC patients using PROMs in the assessment. Methodological and reporting quality was in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. This systematic review was performed as part of phase 1 of the development of a European Organisation for Research and Treatment of Cancer QoL questionnaire for VC patients. Results: The search revealed 2299 relevant hits, with 11 articles extracted including a total of 535 women with VC; no randomized controlled trials were identified. The selected studies exhibited great heterogeneity in terms of PROMs use. Twenty-one different instruments assessed QoL. Most of the questionnaires were generic. Different issues (sexuality, lymphedema, body image, urinary and bowel function, vulva-specific symptoms) were reported as potentially important, but the results were not systematically collected. Only one VC-specific questionnaire was identified but did not allow for assessment and reporting on a scale level. Conclusions: Vulva cancer treatment is associated with considerable morbidity deteriorating QoL. To date, there is no validated PROM available that provides adequate coverage of VC-related issues. The study confirms the need for a VC-specific QoL instrument with sensitive scales that allows for broad cross-cultural application for use in clinical trials.